Dry storeroom no. 1 : the secret life of the Natural History Museum - Fortey, Richard A. (Alfred A. Knopf, 2008)
In an elegant and illuminating narrative, Fortey acquaints the reader with the extraordinary people, meticulous research and driving passions that helped to create the timeless experiences of wonder that fill London's Natural History Museum. And with the museum's hallways and collection rooms providing a dazzling framework, Fortey offers an often eye-opening social history of the scientific accomplishments of the nineteenth, twentieth and twenty-first centuries.--From publisher description.